2020
DOI: 10.1002/ncp.10604
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Body Composition, and Lung Function in Prepubertal Children with Cystic Fibrosis Diagnosed by Newborn Screening

Abstract: Background Children with cystic fibrosis (CF) are at risk of altered body composition (BC). Newborn screening (NBS) may lead to improved BC outcomes. We investigated BC and its relationship with lung function in prepubertal children diagnosed with CF by NBS. Secondary aims explored predictors of fat‐free mass (FFM) and lung function. Methods Thirty‐seven screened (non‐meconium ileus) children with CF (20 boys) born 2007–2012 had a dual‐energy x‐ray absorptiometry scan at 5–8 years to determine whole‐body (WB) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Failure to thrive in early childhood is seminal, also in healthy children since early childhood growth impacts lung function development and is considered to positively affect respiratory health at older ages 18 19 ; associations which have also been demonstrated for CF 11 20 . Our findings on improvements of nutrition by NBS are substantiated by results from other countries, such as the US 18 19 20 and Australia 6 , Canada 5 , the UK 21 and Brazil 13 in many of which NBS has been implemented for much longer time periods, permitting longer follow-up periods and larger cohorts than our analyses.…”
Section: Discussionsupporting
confidence: 81%
“…Failure to thrive in early childhood is seminal, also in healthy children since early childhood growth impacts lung function development and is considered to positively affect respiratory health at older ages 18 19 ; associations which have also been demonstrated for CF 11 20 . Our findings on improvements of nutrition by NBS are substantiated by results from other countries, such as the US 18 19 20 and Australia 6 , Canada 5 , the UK 21 and Brazil 13 in many of which NBS has been implemented for much longer time periods, permitting longer follow-up periods and larger cohorts than our analyses.…”
Section: Discussionsupporting
confidence: 81%
“…They found that 5% of their population had a fat-free mass index (FFMI) z-score of < -1 [near the value of hidden depletion previously published in adult CF studies (69)] despite optimal BMI z-scores. FEV 1 was more strongly associated with whole body FFMI than with BMI (27), supporting the importance of body composition on pulmonary function previously observed in both children and adults (36, 70) (Table 2).…”
Section: The 2020'ssupporting
confidence: 86%
“…Owen et al. reported on body composition and its association with pulmonary function in 37 pre-pubertal children ( 27 ). They found that 5% of their population had a fat-free mass index (FFMI) z-score of < -1 [near the value of hidden depletion previously published in adult CF studies ( 69 )] despite optimal BMI z-scores.…”
Section: The 2020’smentioning
confidence: 99%
“…Short height can be caused by skeletal dysplasia, sexual precocity, malnourishment, and iatrogenic factors such as chemotherapy, radiation, glucocorticoids, and surgery ( Table 1 ). SGA and intrauterine growth retardation are both associated with growth retardation ( 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ). In addition, toward being an indication of a child's physical health, small stature can have a detrimental effect on a child's mental health.…”
Section: Literature Reviewmentioning
confidence: 99%